Biosensing Systems Based on Graphene Oxide Fluorescence Quenching Effect - Antonella Battisti; Sangram Keshari Samal; Dario Puppi (Micromachines, 2023)
Graphene oxide (GO) is a versatile material obtained by the strong oxidation of graphite. Among its peculiar properties, there is the outstanding ability to significantly alter the fluorescence of many common fluorophores and dyes. This property has been exploited in the design of novel switch-ON and switch-OFF fluorescence biosensing platforms for the detection of a plethora of biomolecules, especially pathological biomarkers and environmental contaminants. Currently, novel advanced strategies are being developed for therapeutic, diagnostic and theranostic approaches to widespread pathologies caused by viral or bacterial agents, as well as to cancer. This work illustrates an overview of the most recent applications of GO-based sensing systems relying on its fluorescence quenching effect.